Value Engineering-Based Chip Cutting Machine for Rural UMKM Productivity - Dimas Eka Prasetyo Susanton; Boy Isma Putra (Indonesian Journal of Cultural and Community Development, 2025)
General Background: Rural food-processing UMKM frequently face production bottlenecks due to limited and inefficient equipment. Specific Background: In Wonosunyo Village, cassava chip production relies on manual cutting, causing long processing times and unmet market demand. Knowledge Gap: Previous studies rarely quantify cost–function trade-offs when repurposing existing machines for UMKM-scale production. Aims: This study analyzes the modification of an existing selep machine into a cassava chip cutting machine using the Value Engineering method to achieve optimal function with minimal cost. Results: The modified machine reduced cutting constraints, offered additional functional features, and required a total cost of IDR 1,434,000, substantially lower than commercially available machines priced at IDR 9,500,000. Novelty: The study demonstrates a systematic Value Engineering application that maximizes underutilized village machinery into a multifunctional production tool. Implications: The findings provide a practical model for cost-efficient technological development that supports productivity and sustainability of rural UMKM without heavy capital investment.